Discovery of isoquinolinone and naphthyridinone-based inhibitors of poly(ADP-ribose) polymerase-1 (PARP1) as anticancer agents: Structure activity relationship and preclinical characterization. Issue 24 (15th December 2020) - Karche, Navnath P.; Bhonde, Mandar; Sinha, Neelima; Jana, Gourhari; Kukreja, Gagan; Kurhade, Sanjay P.; Jagdale, Arun R.; Tilekar, Ajay R.; Hajare, Anil K.; Jadhav, Ganesh R.; Gupta, Nishant R.; Limaye, Rohan; et al.
Graphical abstract: Abstract: The exploitation of GLU988 and LYS903 residues in PARP1 as targets to design isoquinolinone (I & II) and naphthyridinone (III) analogues is described. Compounds of structure I have good biochemical and cellular potency but suffered from inferior PK. Constraining the linear propylene linker of structure I into a cyclopentene ring (II) offered improved PK parameters, while maintaining potency for PARP1. Finally, to avoid potential issues that may arise from the presence of an anilinic moiety, the nitrogen substituent on the isoquinolinone ring was incorporated as part of the bicyclic ring. This afforded a naphthyridinone scaffold, as shown in structure III. Further optimization of naphthyridinone series led to identification of a novel and highly potent PARP1 inhibitor 34, which was further characterized as preclinical candidate molecule. Compound 34 is orally bioavailable and displayed favorable pharmacokinetic (PK) properties. Compound 34 demonstrated remarkable antitumor efficacy both as a single-agent as well as in combination with chemotherapeutic agents in the BRCA1 mutant MDA-MB-436 breast cancer xenograft model. Additionally, compound 34 also potentiated the effect of agents such as temozolomide in breast cancer, pancreatic cancer and Ewing's sarcoma models.